Trapping tetracycline loaded nanoparticles into polycaprolactone fiber networks for periodontal regeneration therapy. - Wan Abdul Khodir, WK; Guarino, V; Alvarez Perez, MA; Cafiero, C; Ambrosio, L (SAGE, 2013)

(untitled)
The controlled delivery of antibiotics, anti-inflammatory agents, or chemotherapeutic agents to the periodontal site is a recognized strategy to improve the efficiency of regenerative processes of hard tissues. A novel approach based on the trapping of tetracycline hydrochloride–loaded particles in polycaprolactone nanofibers was used to guide the regeneration processes of periodontal tissue at the gum interface. Chitosan nanoparticles loaded with different levels of tetracycline hydrochloride (up to 5% wt) were prepared by solution nebulization induced by electrical forces (i.e. electrospraying). The fine tuning of process parameters allows to obtain nanoparticles with tailored sizes ranging from 0.485 ± 0.147 μm to 0.639 ± 0.154 μm. The tetracycline hydrochloride release profile had a predominant burst effect for the first 70% of release followed by a relatively slow release over 24 h, which is promising for oral drug delivery. We also demonstrated that trapping tetracycline hydrochloride–loaded particles with submicrometer diameters into a polycaprolactone fiber network contributed to slowing the release of tetracycline hydrochloride from the nanoparticles, thus providing a more prolonged release in the periodontal pocket during clinical therapy. Preliminary studies on human mesenchymal stem cells confirm the viability of cells up to 5 days after culture, and thereby, validate the use of nanoparticle-/nanofiber-integrated systems in periodontal therapies